Penggunaan Jamur (Trichoderma sp. dan Beauveria bassiana) Terhadap Hama Kutu Kebul (Bemisia tabaci Genn.) pada Fase Vegetatif Tanaman Melon(Cucumis melo L.): Fungal Control of Whitefly (Bemisia tabaci Genn.) Using Trichoderma sp. and Beauveria bassiana in Vegetative-Stage Melon (Cucumis melo L.) - Muhammad Faisal Setiawan; Wuye Ria Andayanie; Ratna Mustika Wardhani (Universitas Merdeka Madiun, 2025)
Melon (Cucumis melo L.) is a high – value horticultural commodity with increasing demand. One of the main challenges in melon cultivation is infetstation by whitefly (Bemisia tabaci Genn.) which causes direct damage and acts as a virus vector. This study aimed to evaluate the effect of Trichoderma sp. and Beauveria bassiana on the vegetative growth of melon and the suppression of whitefly infestasion. The experiment was arranged in a Completely Randomized Design (CRD) with four treatments : control (P0), Trichoderma sp. (P1), Beauveria bassiana (P2), and their combination (P3), each repeated three times with nine plants per replicate. Observed parameters included spore density, spore viability, plant growth (height, stem diameter, number of leaves, and flowers), whitefly population, and leaf damage intensity. The results showed that the combination treatment (P3) produced the best outcome, with plant height of 149,85 cm, stem diameter of 0,68 cm, higher leaf and flower number compared to control, although not statistically significant. More over, the combination effectly reduced whitefly populations from 49,66 to 10,55 insects per plant at 49 days after transplanting, and decreased leaf damage intensity below the control threshold. Both fungi exhibited spore viability above 90%, indicating good inoculum quality. These findings suggest that the combined application of Trichoderma sp. and B. bassiana has potential as an environmentally friendly integrated pest management (IPM) strategy for melon cultivation under greenhouse conditions.